Competent demand pull and technological flows within sectoral systems: the evidence on differences within Europe. (27th March 2019) - Antonelli, Cristiano; Gehringer, Agnieszka
Abstract: The paper implements the competent demand-pull hypothesis that grafts the advances of the economics of knowledge on the Kaldor–Schmookler demand-pull approach. Demand-pulling effects occur only if the increase of derived demand for both capital and intermediary inputs is accompanied by knowledge interactions carried by market transactions. The competent demand-pull hypothesis rejuvenates the standard demand-pull approach through the focus on the sectoral architecture of market-embedded inter-sectoral knowledge linkages between competent users and innovative producers. We measure such market-embedded and competent influence with the derived demand for intermediates—taken from input–output tables—accounting for productivity increases downstream. The empirical evidence from dynamic panel estimations for the European Union (EU) over the period 1995–2007 suggests the presence of strong and positive competent demand impulses, but the effects vary between three EU sectoral systems, the EU core, the East and the South.